The pdepe solver for analysing the flow of MHD Cu–H2O nanofluid across an oscillating vertical plate - G. Jithender Reddy; V. Ganesh Kumar; M. Anil Kumar (Case Studies in Chemical and Environmental Engineering)
This study investigates the characteristics of an unsteady, incompressible, and electrically conductive flow. The flow consists of H2O based nanofluid that contains suspended sphere-shaped Cu nanoparticles. The flow occurs across an oscillating and porous vertical plate. Simultaneous non-dimensional governing partial differential equations are solved by pdepe solver in MATLAB 22a, accounting for thermophysical properties and relevant parameters. We analyzed the behavior of the Cu -H2O nanofluid in relation to various fundamental parameters, including thermal buoyancy force, kinetic energy, thermal conductivity, volume fraction of nanoparticles, and time. Additionally, we determined the rate of local heat transfer and skin friction of the Cu-water nanofluid, presenting the results in tabular form. Our findings were compared with previously reported results to validate the accuracy and reliability of the pdepe solver. The pdepe solver in MATLAB is a straightforward and convenient tool for simulating and visualizing models, It is an alternative method for solving IBVP of parabolic & hyperbolic.